Peningkatan Hasil Belajar Siswa Prakarya Melalui Model Pembelajaran STEAM - Widyawati, Ria (Jurnal Nispatti, 2025)
The purpose of this research in general is to improve and improve the quality of handcrafted learning and specifically to improve the learning outcomes of handcrafted learning through the Science Technology Engineering Art Mathematics (STEAM) learning method for students in class VIII-F Odd semester SMP Negeri 13 Surakarta in the school year 2019/2020. This research was conducted in two cycles, each cycle consisting of planning, implementing the action, reflecting and evaluating. To know the progress of the learning outcomes of students, each cycle is done by using a Post Test and calculating the average achievement. Analysis of the data used in this study was a qualitative descriptive analysis based on the results of observation and reflection in cycle I and cycle II. The results of the study can be concluded that the application of the STEAM (Science Technology Engineering Art Mathematics) learning method can improve the learning outcomes of workshops for class VIII-F students of SMP Negeri 13 Surakarta from the initial conditions of low learning outcomes, namely with an average of 64.68 to the final condition of learning outcomes. High craftsmanship is with an average of 83.72 with an increase of 19.4%.